Changing Public-Private Dynamics in Polish Higher Education - Kwiek, Marek (International Higher Education, 2016)
The public–private dynamics in systematically contracting Polish higher education has been changing rapidly. In the global context of the increasing reliance on cost-sharing mechanisms and the private sector growth, the Polish system seems to be moving in the opposite direction as our data show. The Polish trend of higher education de-privatization (in funding and enrolments) goes against the global trend of its privatization. The Polish case shows how fragile private higher education is when its dominating demand-absorbing subsector is confronted with a double challenge of changing demographics and massive public financing in the public sector.